Some Negative Effects of Heat Stress in Feedlot Heifers May Be Mitigated via Yeast Probiotic Supplementation - Broadway, Paul R.; Carroll, Jeff A.; Burdick Sanchez, Nicole C.; Cravey, Matt D.; Corley, Jimmie R. (Frontiers in Veterinary Science, 2020)
This study was designed to determine if supplementation of a combination live yeast and yeast cell wall product in feed could mitigate the negative impacts associated with heat stress (HS). Crossbred, phenotypically similar beef heifers (n=32; BW=385±43 kg) were fed a standard finishing ration without (CON) or with a combination of a live yeast (1.5 g/hd/d) and yeast cell wall product (2.5 g/hd/d; YEAST; Phileo Lesaffre Animal Care, Milwaukee, WI). After 50 d of supplementation, heifers were transported to an environmentally-controlled facility and placed in individual bleeding stalls after indwelling jugular catheters and vaginal temperature (VT) loggers were inserted. Heifers were kept in thermoneutral (TN) conditions for 48 h [temperature-humidity index (THI) 67; d1 to 2] then were subjected to HS for 4 d (peak THI 80; d 3 to 6). From d 2 to 6, hourly blood samples were collected for serum isolation from 1400-1800 h and again from 2200-0200 h which represented the daily targeted peak and nadir of THIs. A whole blood sample was collected twice daily at 1400 and 2200 h for complete blood counts (CBC). There was no difference in BW (P=0.14) or ADG (P=0.53) between the treatments during HS. Yeast-supplemented heifers exhibited reduced VT during HS compared to CON heifers (P<0.01). There was no difference in water intake during the TN phase (P=0.25); however, YEAST heifers consumed more water/h (P<0.01) and had increased drinking bouts (P<0.01) during HS compared to CON heifers. Respiration rates (RR) did not differ (P=0.21) during TN, but YEAST heifers tended (P=0.09) to have decreased RR during HS compared to CON heifers. There were no differences between treatments when evaluating CBC parameters (P≥0.10). There was a tendency (P=0.08) for greater cortisol in the CON than YEAST heifers during HS; however, glucose (P = 0.38) and NEFA (P=0.70) concentrations did not differ. In summary, supplementation of live yeast and yeast cell wall products to feedlot heifers may mitigate some of the negative effects associated with HS in feedlot cattle as observed in decreased RR and VT and increased water intake.